2003
DOI: 10.1108/13612020310464368
|View full text |Cite
|
Sign up to set email alerts
|

Risk perception and e‐shopping: a cross‐cultural study

Abstract: The purpose of this study is to examine first, whether there are differences in risk perception between the USA and Korea, second, whether there are differences in risk perception between apparel purchasers and non‐apparel purchasers across countries, third whether there are differences in the effect of risk factors on purchasing intention between the USA and Korea, and, fourth, whether there are differences in the effect of risk factors on purchasing intention between apparel purchasers and non‐apparel purcha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
61
0
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 82 publications
(65 citation statements)
references
References 30 publications
2
61
0
2
Order By: Relevance
“…Although lack of prior literature in the similar domain makes it difficult to compare results of this research with previous findings, it can be linked to some previous researches on online consumer behavior with respect to risk perception. Few researches on online consumer behavior have identified a negative and strong influence of risk perception on intention of online purchasing [35,[44][45][46][47][48]. However, this study has identified a moderate negative association between risk perception and online impulse buying tendency.…”
Section: Discussionmentioning
confidence: 53%
“…Although lack of prior literature in the similar domain makes it difficult to compare results of this research with previous findings, it can be linked to some previous researches on online consumer behavior with respect to risk perception. Few researches on online consumer behavior have identified a negative and strong influence of risk perception on intention of online purchasing [35,[44][45][46][47][48]. However, this study has identified a moderate negative association between risk perception and online impulse buying tendency.…”
Section: Discussionmentioning
confidence: 53%
“…Numerous studies have confirmed that perceived risk affects consumers' attitudes (Featherman & Pavlou, 2003;Lee, Kim, & Fiore, 2010;Park & Kim, 2007;Verhagen, Meents, & Tan, 2006) and purchase intentions (Choi & Lee, 2003;Gaal & Burns, 2001;Han & Chung, 2014;Jin & Koh, 1999;Park, Lennon, & Stoel, 2005). For instance, two online shopping studies found that perceived risk negatively influenced attitudes toward online retailers (Lee et al 2010;Verhagen et al, 2006).…”
Section: Perceived Risk Attitudes and Purchase Intentionsmentioning
confidence: 88%
“…Studies such as those conducted by Hisrich, Dornoff and Kernan (1972) and Choi and Lee (2003) have shown that the perception of risk affects a consumer's propensity to make a buying decision. In this sense, when consumers perceive risks, they assess those risks before making a decision (Weegels & Kanis, 2000).…”
Section: H6mentioning
confidence: 99%